Profil Swamedikasi Analgesik di Masyarakat Surabaya, Jawa Timur - Stevan Victoria Halim; Antonius Adji Prayitno S; Yosi Irawati Wibowo (Fakultas Farmasi Universitas Pancasila, 2018)
Self-medication is one of the patient's efforts to treat the symptoms or health problems with drug without using a prescription. The most often class of drugs used as self-medication is analgesic (36,2-59,0%). Aim of this study is to describe analgesic self-medication profile among East Surabaya communities, especially Mulyorejo subdistrict. This study is an observational descriptive study that involving 225 patients from 9 pharmacies. The data were collected by using validated questionnaire contains sociodemographic profiles, the frequency of using analgesic, and analgesic profiles purchased by the patients. The data analyze was perfomed by comparing the average of analgesic self-medication frequency based on the patients sociodemographic profiles. The results showed that the average frequency of analgesic used as self-medication is 10.71 (95% CI 8.81-12.60) times a month. The average frequency of analgesic used as self-medication may differ based on sociodemographic profiles. Male patients, elderly, low education level, unemployed, low income (< 2 million), living alone/ divorce, having history of smoking or drinking alcohol showed a higher average frequency of self-medication than the other groups. The results of the study related to analgesic profile showed the majority of patients (80.00%) bought 1 type of analgesic. The most common analgesic group (67.03%) purchased by the patient is Non-Steroidal Anti-Inflammatory Drugs (NSAIDs). Headache (42.22%) is a symptom that often encourages patients to use analgesic as self-medication. Based on the results of the study, education about the use of analgesic as self-medication can be more focused on groups of patients with a particular sociodemographic background and NSAIDs drug groups. It aims to avoid the less responsible use of analgesic as self-medication.